An Analysis of Indonesian-Eglish Code Mixing Used in Social Media (TWITTER) - Cindy Nabila; Andi Idayani (J-SHMIC : Journal of English for Academic, 2022)
This study entitled An Analysis of Indonesian-English Code Mixing on Social Media was examined by the researcher (Twitter). The goal of this study is to determine the form and function of Indonesian-English code-mixing on Twitter. A descriptive qualitative method was used to perform this study. The data for this study employed the tweets of influential people on Twitter. The instrument utilized by this researcher was documentation. This study was carried out entirely online, primarily on Twitter. The influencers' tweets were screenshotted by the researcher. The data was then categorized as code-mixing by the researcher. The findings showed that there are six forms of code-mixing in Twitter, such as code-mixing of Word 53 data, code-mixing of Phrase 20 data, code-mixing of Hybrid 8 data, code-mixing of Word Reduplication 1 data, code-mixing of Idiom 7 data, code-mixing of Clause 25 data. The researcher found some relevant purposes of code-mixing in Twitter. They are need feeling motive, be more informative, make jokes, expressing their emotions.